An autonomous approach to observing the seasonal ice zone in the western arctic - Lee, Craig M.; Thomson, Jim; Cho, Kyoung Ho; Cole, Sylvia; Doble, Martin; Freitag, Lee; Graber, Hans; Hwang, Byongjun; Jayne, Steve; Kang, Sung Ho; Kim, Joo Hong; Krishfield, Rick; et al. (Oceanography, 2017)
The Marginal Ice Zone and Arctic Sea State programs examined the processes that govern evolution of the rapidly changing seasonal ice zone in the Beaufort Sea. Autonomous platforms operating from the ice and within the water column collected measurements across the atmosphere-ice-ocean system and provided the persistence to sample continuously through the springtime retreat and autumn advance of sea ice. Autonomous platforms also allowed operational modalities that reduced the field programs’ logistical requirements. Observations indicate that thermodynamics, especially the radiative balances of the ice-albedo feedback, govern the seasonal cycle of sea ice, with the role of surface waves confined to specific events. Continuous sampling from winter into autumn also reveals the imprint of winter ice conditions and fracturing on summertime floe size distribution. These programs demonstrate effective use of integrated systems of autonomous platforms for persistent, multiscale Arctic observing. Networks of autonomous systems are well suited to capturing the vast scales of variability inherent in the Arctic system.
CRIS-Team Scopus Importer:2024-03-18